Micron-sized mesoporous carbon spheres with uniform particle size and preparation method thereof

A hydro(solvent)thermal method using aromatic compounds and additives achieves uniform micron-sized mesoporous carbon spheres, addressing size control issues and reducing costs, suitable for chromatography and other applications.

CN119191258AInactive Publication Date: 2024-12-27SUZHOU CLEAN CARBON NANO MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411237268.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for preparing micron-sized mesoporous carbon spheres face challenges such as wide particle size distribution, frequent adhesion, and difficulty in controlling uniformity, particularly when scaling up to submicron or micron scales, leading to increased production costs and material wastage.

Method used

A hydro(solvent)thermal method using aromatic compounds, aldehydes, surfactants, and organic additives to form micron-mesoporous polymer spheres, followed by heat treatment, which controls particle size and prevents agglomeration, resulting in uniform micron-sized mesoporous carbon spheres with specific surface area and pore characteristics.

Benefits of technology

The method produces high-quality, uniformly sized mesoporous carbon spheres suitable for chromatography fillers and other applications, reducing production costs and simplifying processes, with potential for industrial scale-up.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191258A_ABST
    Figure CN119191258A_ABST
Patent Text Reader

Abstract

The invention discloses micron-sized mesoporous carbon spheres with uniform particle size and a preparation method thereof. The preparation method has the advantages of simple process, low cost, easiness in amplification and the like. According to the preparation method, an aromatic compound and an aldehyde compound are taken as raw materials, a block copolymer is taken as a soft template, all the components play a synergistic effect, micron-mesoporous polymer spheres with uniform and controllable sizes are synthesized, and then high-quality micron-mesoporous carbon spheres with uniform sizes are obtained through heat treatment. The defect that uniform carbon microspheres cannot be synthesized due to the fact that particles are easy to coagulate after being enlarged in a soft template method in the prior art is overcome. The size of the prepared carbon spheres is 1-5 [mu] m, the aperture is 2-50 nm, and the prepared carbon spheres have the characteristics of uniform size, concentration and the like, and have wide application prospects in the fields of chromatographic fillers, lithium ion batteries, electrode materials, catalyst carriers, energy storage materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a micron-sized mesoporous carbon sphere with uniform particle size and a preparation method thereof, and belongs to the technical field of preparation of novel carbon materials. Background Art

[0002] Micron mesoporous carbon sphere is a new functional material with good chemical stability and thermal stability, and has the characteristics of excellent electrical and thermal conductivity, high specific surface area and low density. Coupled with its regular spherical structure, it has become a material with broad application prospects and is widely used in chromatographic fillers, lithium-ion batteries, electrode materials, catalyst carriers, energy storage materials and other fields (Mater. Today Sustain. 2022, 1 8, 1 001 36; Int. J. Biol. Macromol. 2021, 1 70, 751-767; Energy Storage Mater. 2020, 32, 65-90). For liquid chromatography filler applications, the particle size and uniformity of the filler have an important influence on the separation results. The reduction of particle size can increase the number of plates and thus increase the separation effect, and the improvement of the uniformity of the microsphere size can effectively improve the resolution of the chromatography column. If the particle size is not uniform, during the separation process, small-particle fillers will gather in the gaps between large-particle fillers in the column, increasing the separation pressure, and in severe cases, separation cannot be performed. Fillers with uneven particle sizes need to be screened before they can be used as separation media, which not only wastes raw materials but also increases production costs. In addition, carbon microspheres of a few microns are difficult to screen, and even if they are screened, the uniformity of their particle size is still not high, which will bring many difficulties to practical applications. If micron-mesoporous carbon spheres with uniform particle size can be prepared, the operating procedures will be greatly simplified, raw materials will be saved, and production costs will be reduced.

[0003] At present, the main methods for preparing micron carbon spheres are: hydrothermal method, chemical vapor deposition method (CVD method), template method, mechanical ball milling method, ultrasonic method and arc discharge method. Hydrothermal method refers to the process in which a series of chemical reactions occur in the solvent of the raw material molecules in a sealed pressure vessel to form a micron carbon sphere precursor, and then carbonization is performed to obtain micron carbon spheres. It has the advantages of safety, non-toxicity, simple process flow and high product purity. The traditional hydrothermal method for preparing micron carbon spheres generally uses small molecular biomass such as sucrose and glucose as carbon sources, and forms carbonized spheres through a series of chemical reactions such as dehydration, cracking, cyclocondensation, etc. Because the raw material source of this method is very rich and cheap, and the reaction solvent is water, the product has minimal environmental pollution and the process is simple, it has attracted widespread attention. However, the hydrothermal method reported so far still has some limitations, such as a wide range of particle size distribution, frequent adhesion between spheres, and pores mainly being micropores.

[0004] Further research has found that using phenolic compounds as raw materials and block copolymers as soft templates, mesoporous polymer nanospheres are synthesized by hydrothermal method, and then subjected to high-temperature pyrolysis to obtain mesoporous nanocarbon spheres with uniform particle size (Nat. Mater. 2015, 14, 763-774). However, when the polymer spheres reach submicron or even micron scales, the polymer spheres are prone to coagulation, making it difficult to control the size of the polymer spheres, resulting in uneven carbon sphere size. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a micron-sized mesoporous carbon sphere with uniform particle size and a preparation method thereof by a hydro(solvothermal) method.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention first discloses a method for preparing micron-sized mesoporous carbon spheres with uniform particle size, comprising the following steps:

[0008] S 1. Dissolve the aromatic compound, aldehyde compound and surfactant separately, mix them to form a mixed solution, and then add additives under stirring, wherein the mass ratio of the aromatic compound, aldehyde compound, surfactant and additive is 1:0.3-0.8:0.7-1.3:0.8-4;

[0009] S2, heating the mixed solution to 80-120° C. under stirring conditions to form micron-mesoporous polymer spheres;

[0010] S3, raising the temperature to 300-1200° C., heat-treating the micron-mesoporous polymer spheres to obtain micron-sized mesoporous carbon spheres with uniform particle size.

[0011] Preferably, the aforementioned aromatic compound contains at least one hydroxyl group selected from one or more of phenyl compounds, naphthyl compounds or anthracene compounds.

[0012] More preferably, the aforementioned aromatic compound is selected from one or more of phenol, resorcinol, aminophenol, p-hydroxybenzoic acid, 2,4-dihydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 3,7-dihydroxy-2-naphthoic acid and the like.

[0013] More preferably, the aldehyde compound is formaldehyde or a compound that can be decomposed into formaldehyde, and an aldol condensation reaction occurs during the polymerization process. Specifically, hexamethylenetetramine or formaldehyde can be selected.

[0014] More preferably, the solvent is a mixed solvent of water and any one or more of methanol, ethanol, acetone, isopropanol and tetrahydrofuran.

[0015] Further preferably, the aforementioned surfactant is selected from one or more of the amphiphilic block copolymers, wherein the copolymer satisfies that the hydrophobic segment contains at least three carbon atoms, such as P123 and F127, and one or two thereof can be selected.

[0016] Further preferably, the aforementioned additive is a C6 to C20 organic compound molecule, such as one or more of oleic acid, oleylamine, 2-methylimidazole, quinoline, mesitylene, toluene, ethylbenzene, 2-ethylaniline, and ethyl 3-mercaptopropionate.

[0017] Still more preferably, in the aforementioned step S2, the polymerization reaction temperature is 80-120° C., the reaction time is 20-30 h, and the stirring rate is 300-800 rpm.

[0018] More preferably, in the aforementioned step S3, the temperature of the heat treatment is 300-1200°C, the time is 1-10h, and the atmosphere of the heat treatment includes at least one of Ar, N2, He and a mixture of H2 and an inert atmosphere.

[0019] The present invention also discloses a micron-sized mesoporous carbon sphere with uniform particle size prepared by the above method, wherein the micron-sized mesoporous carbon sphere has a diameter of 1 to 5 μm, a pore size of 2 to 50 nm, and a pore volume of 0.1 to 3 cm 3 ·g -1 , with a specific surface area of ​​50 to 1500 m 2 ·g -1 .

[0020] The present invention is beneficial in that:

[0021] (1) The present invention uses a hydro (solvent) thermal method assisted by additives (organic molecules) to synthesize micron mesoporous polymer spheres with uniform and controllable size using aromatic compounds and phenolic compounds as raw materials and block copolymers as soft templates, and then obtains high-quality micron mesoporous carbon spheres with uniform size through heat treatment, thereby overcoming the defects of the soft template method in the prior art that the particles are easy to aggregate after becoming larger and cannot synthesize uniform carbon microspheres. In the polymerization process of the present invention, the applicant surprisingly found that the additive can play a synergistic role with the surfactant, control the size of the carbon spheres by adjusting the surface tension of the mixed solvent, and can also enrich the polymer surface, stabilize the particles, and effectively prevent the polymer from agglomerating, thereby solving the problem of uneven particle size of micron carbon spheres prepared by the hydro (solvent) thermal method in the prior art. The organic additive can also enter the hydrophobic end of the surfactant and interact with the hydrophobic end, so that the formed micelles become larger, thereby playing a pore expansion role and increasing the pore size.

[0022] (2) The carbon spheres prepared by the present invention have a size of 1 to 5 μm, a pore diameter of 2 to 50 nm, and a pore volume of 0.1 to 3 cm 3 ·g -1, with a specific surface area of ​​50 to 1500 m 2 ·g -1 It has the characteristics of uniform size and concentration, filling the gap in carbon-based liquid chromatography fillers. It can also be widely used in lithium-ion batteries, electrode materials, catalyst carriers, energy storage materials and other fields. Its preparation method has the advantages of simple process, low cost and easy scale-up, and is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a SEM image of the micron mesoporous carbon spheres prepared in Example 1 of the present invention (scale 1 μm);

[0024] Figure 2 is a SEM image of the micron mesoporous carbon spheres prepared in Example 1 of the present invention (scale 40 nm);

[0025] Figure 3 is a TEM image of the micron mesoporous carbon spheres prepared in Example 1 of the present invention;

[0026] Figure 4 is a nitrogen physical adsorption diagram of the micron mesoporous carbon spheres prepared in Example 1 of the present invention;

[0027] Figure 5 It is a SEM picture of the micron mesoporous carbon spheres prepared in the comparative example of the present invention. DETAILED DESCRIPTION

[0028] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0029] Unless otherwise specified in the present invention, all raw materials used are commercially available.

[0030] Example 1

[0031] 1.3 g of 3-aminophenol, 0.8 g of F127, 0.27 g of P123, and 0.56 g of hexamethylenetetramine were dispersed and dissolved in 80 mL of ethanol-water (volume ratio of 1 / 1), and 2.0 mL of mesitylene was added to the mixed solution while stirring;

[0032] The temperature was raised to 100°C and stirred at 500 rpm for 24 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain micron-sized polymer spheres. The temperature was raised to 800°C in an argon atmosphere and carbonized for 3 hours to obtain micron-sized mesoporous carbon spheres.

[0033] The SEM and TEM images of the micron-sized mesoporous carbon spheres are shown in Figure 1 to Figure 3 .from Figure 1 and Figure 3 It can be seen that the product size is very uniform, with a diameter of about 1.5μm. Figure 2It can be seen that its surface is rich in mesopores. Figure 4 , its surface area is calculated to be 150m 2 ·g -1 , pore diameter is 5nm, pore volume is 0.2cm 2 ·g -1 The specific characterization results are shown in Table 1.

[0034] Example 2

[0035] Disperse and dissolve 1.3 g of resorcinol, 0.8 g of F127, 0.27 g of P123, and 0.48 g of hexamethylenetetramine in 80 mL of methanol-water (volume ratio of 1 / 1), and add 2.0 mL of mesitylene to the mixed solution while stirring;

[0036] The temperature was raised to 100°C and stirred at 300 rpm for 24 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain micron-sized polymer spheres. The temperature was raised to 800°C in a 5% NH3 / Ar atmosphere and carbonized for 3 hours to obtain micron-sized mesoporous carbon spheres. The specific characterization results of the product are shown in Table 1.

[0037] Example 3

[0038] 1.3 g of 3-aminophenol, 0.27 g of F127, 0.28 g of P123, and 0.64 g of hexamethylenetetramine were dissolved and dispersed in 80 mL of ethanol-water (volume ratio of 1 / 1), and 0.5 mL of oleic acid was added to the mixed solution while stirring;

[0039] The temperature was raised to 80°C and stirred at 700 rpm for 24 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain micron-sized polymer spheres. The micron-sized mesoporous carbon spheres were obtained by carbonizing at 800°C for 3 hours under a nitrogen atmosphere. The specific characterization results of the products are shown in Table 1.

[0040] Example 4

[0041] 1.3 g phenol, 0.8 g F127, 0.27 g P123, and 0.56 g hexamethylenetetramine were dissolved and dispersed in 80 mL ethanol-water (volume ratio of 3 / 1), and 3.0 mL mesitylene was added to the mixed solution while stirring;

[0042] The temperature was raised to 80°C and stirred for reaction for 10 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain micron-sized polymer spheres. The micron-sized mesoporous carbon spheres were obtained by carbonization at 800°C for 3 hours under an argon atmosphere. The specific characterization results of the products are shown in Table 1.

[0043] Example 5

[0044] Dissolve 1.3 g 2,4-dihydroxybenzoic acid, 0.27 g F127, 0.80 g P123, and 0.72 g formaldehyde in 80 mL ethanol-water (volume ratio is 1 / 3), and add 1.0 mL mesitylene to the mixed solution while stirring;

[0045] The temperature was raised to 120°C and stirred at 600 rpm for 22 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain micron-sized polymer spheres. The micron-sized mesoporous carbon spheres were obtained by carbonization at 800°C for 3 hours in a 5% CO2 / Ar atmosphere. The specific characterization results of the products are shown in Table 1.

[0046] Example 6

[0047] 1.3 g 3-aminophenol, 0.27 g F127, 0.80 g P123, and 0.82 g hexamethylenetetramine were dissolved and dispersed in 80 mL ethanol-water (volume ratio of 3 / 1), and 0.5 mL oleylamine was added to the mixed solution while stirring;

[0048] The temperature was raised to 100°C and stirred at 500 rpm for 24 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain micron-sized polymer spheres. The micron-sized mesoporous carbon spheres were obtained by carbonizing at 800°C for 3 hours in an argon atmosphere. The specific characterization results of the products are shown in Table 1.

[0049] Example 7

[0050] 1.3 g of resorcinol, 0.8 g of F127, 0.27 g of P123, and 0.90 g of hexamethylenetetramine were dissolved and dispersed in 80 mL of methanol-water (volume ratio of 1 / 1), and 2.0 mL of toluene was added to the mixed solution while stirring;

[0051] The temperature was raised to 80°C and stirred at 300 rpm for 24 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain micron-sized polymer spheres. The micron-sized mesoporous carbon spheres were obtained by carbonizing at 800°C for 3 hours in an argon atmosphere. The specific characterization results of the products are shown in Table 1.

[0052] Example 8

[0053] 1.3 g 2,4-dihydroxybenzoic acid, 0.54 g F127, 0.54 g P123, and 0.48 g formaldehyde were dissolved and dispersed in 80 mL acetone-water (volume ratio of 1 / 3), and 1.0 mL 2-ethylaniline was added to the mixed solution while stirring;

[0054] The temperature was raised to 120°C and stirred at 600 rpm for 22 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain micron-sized polymer spheres. The micron-sized mesoporous carbon spheres were obtained by carbonizing at 800°C for 3 hours in an argon atmosphere. The specific characterization results of the products are shown in Table 1.

[0055] Comparative Example

[0056] 1.3 g of aminophenol, 0.8 g of F127, 0.27 g of P123, and 0.56 g of hexamethylenetetramine were dissolved and dispersed in 80 mL of ethanol-water (volume ratio of 1 / 1), heated to 100 ° C, and stirred at 500 rpm for 24 hours. After the reaction, centrifuged, washed, and dried to obtain micron-sized polymer spheres, which were carbonized at 800 ° C for 3 hours under argon atmosphere to obtain micron-sized mesoporous carbon spheres.

[0057] The SEM image of the polymer sphere is shown in Figure 5 It is obvious from the figure that the product sizes are different and the particle sizes are uneven. The specific characterization results of the products are shown in Table 1.

[0058] Serial number Diameter(μm) <![CDATA[Surface area (m 2 g -1 )]]> Pore ​​size (nm) <![CDATA[Pore volume (cm 2 g -1 )]]> Particle size uniformity Example 1 1.5 150 5 0.2 Uniform particle size Example 2 1.8 1400 4 1.1 Uniform particle size Example 3 4.5 300 5 0.3 Uniform particle size Example 4 3.8 250 10 0.2 Uniform particle size Example 5 1.1 1100 8 1.3 Uniform particle size Example 6 2.6 800 12 0.6 Uniform particle size Example 7 2.1 400 6 0.7 Uniform particle size Example 8 3.1 500 5 0.4 Uniform particle size Comparative Example 0.2~3 200 3 0.1 Uneven particle size

[0059] Table 1 Product characterization results of Examples 1-8 and Comparative Examples

[0060] As can be seen from Table 1, the products obtained in Examples 1 to 8 all have the characteristics of uniform size and concentration, while the products in the comparative examples have different sizes and very uneven particle sizes. Figure 5 Among them, in Example 2 and Example 5, ammonia or carbon dioxide is used for treatment during calcination, which can further expand the surface area and pore volume of the product.

[0061] In summary, the preparation method of the present invention can obtain high-quality micron mesoporous carbon spheres of uniform size, and the additives used can play a synergistic role with the surfactant, and the size of the carbon spheres can be controlled by adjusting the surface tension of the mixed solvent. It can also be enriched on the polymer surface, stabilize the particles, and effectively prevent the polymer from flocculating, thereby solving the problem of uneven particle size of micron carbon spheres prepared by the water (solvent) thermal method in the prior art. Therefore, the products and technologies of the present invention fill the gaps in liquid chromatography fillers in the prior art, and can also be widely used in the fields of lithium ion batteries, electrode materials, catalyst carriers, energy storage materials, etc., and the preparation method thereof has the advantages of simple process, low cost, and easy amplification, and is suitable for industrial promotion and application.

[0062] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing micron-sized mesoporous carbon spheres with uniform particle size, characterized in that: The steps include: S1, dissolving the aromatic compound, the aldehyde compound and the surfactant respectively, mixing them into a solution, and then adding the additive while stirring, wherein the mass ratio of the aromatic compound, the aldehyde compound, the surfactant and the additive is 1:0.3-0.8:0.7-1.3:0.8-4; S2, heating the mixed solution to 80-120° C. under stirring conditions to form micron-mesoporous polymer spheres; S3, raising the temperature to 300-1200° C., heat-treating the micron-mesoporous polymer spheres obtained in step S2 to obtain micron-sized mesoporous carbon spheres with uniform particle size.

2. The method for preparing micron-sized mesoporous carbon spheres with uniform particle size according to claim 1, characterized in that: The aromatic compound contains at least one hydroxyl group and is selected from one or more of phenyl compounds, naphthyl compounds or anthracene compounds.

3. The method for preparing micron-sized mesoporous carbon spheres with uniform particle size according to claim 1, characterized in that: The aromatic compound is selected from one or more of phenol, resorcinol, aminophenol, p-hydroxybenzoic acid, 2,4-dihydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 3,7-dihydroxy-2-naphthoic acid and the like.

4. The method for preparing micron-sized mesoporous carbon spheres with uniform particle size according to claim 1, characterized in that: The aldehyde compound is formaldehyde or a compound that can be decomposed into formaldehyde.

5. The method for preparing micron-sized mesoporous carbon spheres with uniform particle size according to claim 1, characterized in that: The solvent is a mixed solvent of water and any one or more of methanol, ethanol, acetone, isopropanol and tetrahydrofuran.

6. The method for preparing micron-sized mesoporous carbon spheres with uniform particle size according to claim 1, characterized in that: The surfactant is selected from one or more of the amphiphilic block copolymers, and the copolymer satisfies that the hydrophobic segment portion contains at least three carbon atoms and is selected from one or more of P123 and F127.

7. The method for preparing micron-sized mesoporous carbon spheres with uniform particle size according to claim 1, characterized in that: The additive is an organic compound molecule of C6 to C20, such as one or more of oleic acid, oleylamine, 2-methylimidazole, quinoline, mesitylene, toluene, ethylbenzene, 2-ethylaniline, and ethyl 3-mercaptopropionate.

8. The method for preparing micron-sized mesoporous carbon spheres with uniform particle size according to claim 1, characterized in that: In the step S2, the polymerization reaction temperature is 80-120° C., the reaction time is 20-30 hours, and the stirring rate is 300-800 rpm.

9. The method for preparing micron-sized mesoporous carbon spheres with uniform particle size according to claim 1, characterized in that: In step S3, the heat treatment temperature is 300-1200° C., the time is 1-10 hours, and the heat treatment atmosphere includes at least one of a mixture of Ar, N2, He and NH3, CO2 and H2 and an inert atmosphere.

10. A micron-sized mesoporous carbon sphere with uniform particle size, characterized in that: The micron-sized mesoporous carbon spheres are obtained by the preparation method according to any one of claims 1 to 9, and have a diameter of 1-5 μm, a pore size of 2-50 nm, and a pore volume of 0.1-3 cm 3 ·g -1 , with a specific surface area of ​​50-1500m 2 ·g -1 .